2014
DOI: 10.21236/ada607688
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Physical Fitness Tests and Performance of Military Tasks: A Systematic Review and Meta-Analyses

Abstract: To help evaluate the Army Physical Fitness Test (APFT) and ensure a future test is associated with Soldiers' performance of common physical job requirements, the USAPHC applied a Systematic Review (SR) methodology to identify and synthesize published correlations between military task performance and physical fitness tests. Methods: A preliminary step to our SR was to identify key military-relevant tasks and physical fitness components of interest. Starting with the Army's Warrior Tasks and Battle Drills (WTBD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…The incremental dynamic lift was originally developed by the Air Force. Teves et al reported that the incremental dynamic lift was superior to handgrip strength, isometric 38 cm upright pull strength, body composition, and submaximal prediction of oxygen uptake when predicting job related criterion performance tasks (job requirements involving pulling, pushing, lifting, carrying, and applying torque) (27). Although it was recommended that the Army adopt this test to assess muscle strength before job assignment, the Army did not implement it as a strength test.…”
Section: Aerobic Training (Antonio Duarte)mentioning
confidence: 99%
See 2 more Smart Citations
“…The incremental dynamic lift was originally developed by the Air Force. Teves et al reported that the incremental dynamic lift was superior to handgrip strength, isometric 38 cm upright pull strength, body composition, and submaximal prediction of oxygen uptake when predicting job related criterion performance tasks (job requirements involving pulling, pushing, lifting, carrying, and applying torque) (27). Although it was recommended that the Army adopt this test to assess muscle strength before job assignment, the Army did not implement it as a strength test.…”
Section: Aerobic Training (Antonio Duarte)mentioning
confidence: 99%
“…Examples include a 20-to 30-kg sand and box lift (Canada, Australia, United Kingdom, Germany, and U.S. Marine Corps) and casualty (50-80 kg) drag (15-30 m) (Canada, United Kingdom, and Germany) (27).…”
Section: Aerobic Training (Antonio Duarte)mentioning
confidence: 99%
See 1 more Smart Citation
“…The current heavy sled pull research may be used as a basis for further research into the biomechanical demands of performing other variations of pulling type exercises such as the backward drag. The backward drag technique is used in firefighting and military physical fitness assessments and service, where service people may be required to drag victims out of danger [50, 51]. Further investigation into the biomechanical demands of a vehicle pull may be of benefit to military operations, as soldiers may be faced with instances where they are required to pull/push heavy equipment over short distances [51].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, other activities and different terrains should be investigated in future studies to get better insights of military performance during a broad range of tasks and situations [ 64 ]. The method presented in this study can be directly used for several walking and running activities.…”
Section: Discussionmentioning
confidence: 99%